2020
DOI: 10.3390/rs12142233
|View full text |Cite
|
Sign up to set email alerts
|

Robust Single-Image Haze Removal Using Optimal Transmission Map and Adaptive Atmospheric Light

Abstract: Haze removal is an ill-posed problem that has attracted much scientific interest due to its various practical applications. Existing methods are usually founded upon various priors; consequently, they demonstrate poor performance in circumstances in which the priors do not hold. By examining hazy and haze-free images, we determined that haze density is highly correlated with image features such as contrast energy, entropy, and sharpness. Then, we proposed an iterative algorithm to accurately estimate the extin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Therefore, it is better to exclude this algorithm from our list of benchmarking methods. However, we will demonstrate later in Section 4.3 that the proposed method is comparable to that of Ngo et al [ 21 ] using their reported results.…”
Section: Methodssupporting
confidence: 66%
See 4 more Smart Citations
“…Therefore, it is better to exclude this algorithm from our list of benchmarking methods. However, we will demonstrate later in Section 4.3 that the proposed method is comparable to that of Ngo et al [ 21 ] using their reported results.…”
Section: Methodssupporting
confidence: 66%
“…This section presents a comparative evaluation of the proposed algorithm and four benchmarking methods, including those proposed by He et al [ 7 ], Zhu et al [ 15 ], Kim et al [ 15 ], and Galdran [ 36 ]. As mentioned in Section 1 , although the recent method proposed by Ngo et al [ 21 ] is quite efficient in image quality, its costly computations require considerable effort for future research. Therefore, it is better to exclude this algorithm from our list of benchmarking methods.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations